First‐Line Immune‐Combination Therapy for Driver Gene‐Negative NSCLC With Brain Metastases: Real‐World Outcomes - Mengxing You; Lige Wu; Jiayu Liu; Hanqi Yuan; Zihe Wang; Xuezhi Hao; Puyuan Xing; Junling Li (Thoracic Cancer)
ABSTRACT Background Optimal treatment for driver gene‐negative non‐small cell lung cancer (NSCLC) with brain metastases (BM) remains unclear, particularly regarding immune checkpoint inhibitor (ICI)‐based combinations and local BM therapy. Predictive biomarkers for intracranial efficacy are also undefined. Methods This retrospective study analyzed driver gene‐negative NSCLC patients with BM treated with first‐line ICI‐based systemic therapy (ICI plus chemotherapy [ICI + CT] or ICI + CT plus bevacizumab [ICI + CT + Bev]) from June 2019 to June 2024. The intracranial progression‐free survival (icPFS), progression‐free survival (PFS), and overall survival (OS) were compared between treatment groups and by BM local therapy. The PD‐L1 tumor proportion score (TPS) expression was evaluated for correlation with intracranial efficacy. Results A total of 36 patients were enrolled in the study. The intracranial objective response rate (icORR) was 70.6% (ICI + CT) versus 78.6% (ICI + CT + Bev) (p = 0.689), with no significant differences in icPFS, PFS, or OS between the two different first‐line systemic regimens (all p > 0.05). Local BM therapy (n = 18) did not improve icPFS and OS (all p > 0.05). Extracranial PD‐L1 (TPS ≥ 50%, n = 13) correlated with superior icPFS, PFS, and OS (all p < 0.05) versus PD‐L1 TPS < 50%. Multivariate analysis confirmed PD‐L1 ≥ 50% as an independent prognostic factor (HR = 0.155; 95% CI, 0.025–0.939; p = 0.042). Conclusions Adding bevacizumab to first‐line ICI‐chemotherapy did not enhance survival outcomes. Local treatment for BM did not provide additional survival advantages when combined with first‐line ICI‐based systemic therapy. Extracranial PD‐L1 TPS ≥ 50% predicted improved intracranial efficacy.